2016
DOI: 10.1007/s10875-016-0245-x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Adenosine Deaminase 2 Causes Antibody Deficiency

Abstract: Deficiency of ADA2 (DADA2) has been reported to cause vasculopathy and early-onset stroke. Our case suggests that it should also be considered when evaluating patients with antibody deficiencies and immune dysregulation syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 18 publications
3
72
0
Order By: Relevance
“…A minority of our patients displayed a hypogammaglobulinaemia with a history of recurrent infections, resembling clinical features of patients followed for common variable immunodeficiency (CVID) 21. This finding is likely due to the selection of our patients from the paediatric rheumatology community and should not underestimate the multifaceted phenotype of patients with DADA2, some of whom may display major haematological and/or immunological features of the disease.…”
Section: Discussionmentioning
confidence: 60%
“…A minority of our patients displayed a hypogammaglobulinaemia with a history of recurrent infections, resembling clinical features of patients followed for common variable immunodeficiency (CVID) 21. This finding is likely due to the selection of our patients from the paediatric rheumatology community and should not underestimate the multifaceted phenotype of patients with DADA2, some of whom may display major haematological and/or immunological features of the disease.…”
Section: Discussionmentioning
confidence: 60%
“…As other authors have reported, ADA2 activity might be lower in adults that in children [4,14] and an age-adjusted cut-off value would probably be needed. In our study, as in the study of Schepp et al [19], there was no evidence of an influence of the position and type of mutation on ADA2 enzymatic activity. However, this should also be confirmed by the inclusion of patients with other CECR1 mutations.…”
Section: Doi: 101159/000495794supporting
confidence: 81%
“…Other studies have reported on ADA2 activity in CECR1 single-mutation carriers, and while some authors showed a reduction to approximately half [4,19] other reported no difference in relation to HCs [5,14]. Meanwhile, for serum IgM levels, at the best cut-off of 0.92 g/L, AUC was 0.647 (p = 0.225, 95% CI 0.386-0.908), with a sensitivity of 67.6%, and specificity of 71.4 %, which suggests that this test does not accurately identify CECR1 heterozygous.…”
Section: Doi: 101159/000495794mentioning
confidence: 95%
See 1 more Smart Citation
“…In a subsequent study of 48 cases with polyarteritis nodosa associated with livedo reticularis and/or strokes, Gattorno et al performed Sanger sequencing of CECR1 and determined that 15 cases harboured homozygous or compound heterozygous mutations [88]. Since the time of the original description, there has been an expansion of the clinical phenotype of cases with DADA2, from cytopaenias and pure red cell aplasia [89], to lymphoproliferative disease [90–92], and combined immune deficiency, as well as common variable immune deficiency (CVID) [93]. Indeed, a cohort study of 181 cases with antibody deficiency diagnosed 11 individuals with mutation and enzyme activity confirmed DADA2 [94].…”
Section: Classificationmentioning
confidence: 99%